AGE-STRUCTURE AND ENERGY-RELATED EMISSIONS: RECENT DEMOGRAPHIC CHANGES IN BRAZIL - Polloni-Silva, Eduardo; Cassânego, Vitor Melão; Amancio, Igor Roberto; Ferraz, Diogo; Moralles, Herick Fernando Moralles (Seven Editora, 2025)
This study investigates the effects of the rapid aging process in Brazil, specifically in the São Paulo state, on the CO2 emissions from gasoline and residential energy. This geographic region was chosen precisely because it is one of the country's most densely populated regions and the largest in terms of residents. Therefore, the impact related to human activities is more accurately measured within this environment. This investigation employed a balanced panel dataset with 631 municipalities from 2006-2015, with diagnostic tests, the STIRPAT method, and robustness procedures. Results show that the region does not experience an environmentally friendly aging process, contrary to previous studies conducted on developed economies, and that all age groups positively affect emissions intensity. This outcome allows policymakers to understand the situation better and develop specific initiatives to tackle it accordingly, especially concerning the elderly population. Besides, this manuscript contributes to an ever-growing plethora of knowledge regarding the effects of pollutant emissions on adults in developing countries. DOI: https://doi.org/10.56238/sevened2024.041-021